Decision Support System to Determine the Best Student at MAS Islamic Center in Class XI using a Simple Additive Weighting Method - Thania, Sheila Try; Wayahdi, M. Rhifky; Mughnyanti, Mayang (Journal of Technology and Computer, 2024)
This research aims to develop a Decision Support System (DSS) in determining the best students at MAS ISLAMIC CENTRE by using the Simple Additive Weighting (SAW) method. The SAW method was chosen because of its ability to calculate the number of performance weights on each alternative effectively, allowing comparison of various options based on specified criteria. This research uses a quantitative approach with system development that follows the Waterfall model, starting from the needs analysis stage to implementation and maintenance. The results show that the designed system is able to process student data accurately and display student rankings quickly and efficiently. This provides an advantage for schools in making decisions that are more objective and supported by solid data. The implementation of SAW-based DSS is expected to be a solution that supports transparency and effectiveness in determining the best students in the educational environment.